Membaca Intertekstualitas pada Hasil Renovasi Stasiun Jatinegara Jakarta - Puspitasari, Mutiara Indah; Yusran, Yusfan Adeputera; Titisari, Ema Yunita (RUAS, 2022)
Jatinegara Station is considered as an A class station in Jakarta, which has been around for 111 years since it opened in 1909. This station has been redeveloped in terms of railway facilities and building infrastructure owing to the Double-doubled Track (DDT) project. This renovation attracts discourses in the topic of cultural heritage building’s sustainability, the functionality of the heritage building as an infrastructure building, and the compability of the new concourse building when being compared to the heritage building. Research based on intertextuality study is used to find reasons for development based on the historical and social aspects of today's society. The reasearch of intertextual relationship between the text of Jatinegara Station and the sociohistorical text can provide a further understanding on the renovation in the hope that the public could appreciate the renovations that has been carried out. The methodology used in this research is descriptive with a qualitative approach, the analysis will undergo through suprasegmental and intertextual technique provided by Julia Kristeva. The results is intertextuality reading of renovated Jatinegara Railway Station that is obtained through analyzing the sociohistoric text within.